Tata Kelola dan Kepatuhan Penerapan Standar Patient Safety Penyakit Stroke di Rumah Sakit Dr. Kanujoso Djatiwibowo Tahun 2015 - Iskandar, Edy (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Patient Safety is a system in which hospitals make patient care safer and to prevent injuries caused by medical error due to an action or not taking action that should be taken. The Management of Patient Safety is the Pathway set up as the Patient Safety Standard to be implemented for Stroke disease at Kanujoso Djatiwibowo Hospital Ten Patient Safety standard being studied are Patient Identification, Effective Communication, High Alert Medications, Accuracy of Patient, Procedure and Location of Operation, Hand Hygiene, Fall Risk Patient, Look alike Sound alike Drugs, Accuracy of Drug use, Catheter or Hoses Installation and Disposable syringes, this standard is the combination from The Solution of Patient Safety WHO and The International Patient Safety Goals. This study has successfully formed a Patient Safety Pathway for Stroke disease and analyse the implementation the standard as well.